Relationships among expatriate social network characteristics and performance in overseas assignments: implications for HRD - M.Osman Ghani, Aahad; Rockstuhl, Thomas (2009)
This paper presents the empirical findings of a study that investigated the effects of expatriates' social network characteristics on their perfonnance on overseas assignments. We have used the predictions from social learning theory in explaining the consequences of expatriates' social networks by analyzing relevant field data collected in Singapore. Using matched data of 158 expatriates from seven countries and perfonnance ratings by their supervisors, we find that the number ofhost country nationals in the expatriates' network and the frequency of contact with them predicts supervisory performance ratings. This effect is also mediated by the expatriate's interaction adjustment. We then discuss the implications of these findings for HRD theory and research, as well as for professional practice.